Liquidity - Timothy S. Fuerst (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
This paper develops a general equilibrium model of two traditional explanations of the monetary "black box" linking money and real activity: the liquidity effect and the loanable funds effect. These effects are modeled with a monetary production economy in which central bank injections of cash are funnelled into the economy through the credit market. As a result, only borrowers have direct access to the newly injected cash. The model has several interesting implications: 1) monetary injections cause fluctuations in asset prices for non-Fisherian reasons, 2) monetary injections increase current and future real activity, and, 3) the central bank has the ability to dampen or magnify fluctuations in real activity.
Keywords: 330